The Effect of Distance on Seaweed Growth and Production Using the Strap Rope Method In Pond - Kasnir, Muhammad; Aminuddin, Aminuddin; Nisaa, Khairun (Agrikan Jurnal Agribisnis Perikanan, 2023)
This study examines how spacing affects seaweed Gracilaria sp. growth and productivity using the span rope approach. This study used the longline approach and a randomized block design (RBD) factorial pattern. This study tested plant spacing at 15, 20, and 25 cm. Every treatment used Gracillaria sp. seeds. Each bundle weighs 30 grams. This study studied specific growth, absolute growth, Gracillaria sp. production, and water quality-related research parameters. The study measured absolute and specific seaweed weight increase. These data will be descriptively evaluated using ANOVA and SPSS. The specific growth rate (SGR) was statistically significantly affected by spacing at 15 cm, 20 cm, and 25 cm. The trial results showed that 25 cm spacing had the highest specific daily growth rate, 3.7%. The 15 cm spacing had the lowest growth rate, 1.8%, while the 20 cm spacing had 2.9%. Average absolute growth significantly affected Gracillaria sp. growth. The treatment with the highest average absolute growth rate was 25 cm with 156g, 20 cm with 121g, and 15 cm with 77g.